Pengaruh Kompetensi SDM, Penerapan SIPKD, dan Peran Audit Internal Terhadap Kualitas Laporan Keuangan Pemerintah - Fuji Asih; Hilda Kumala Wulandari; Yenny Ernitawati (JURNAL ILMIAH NUSANTARA, 2024)
This study examines the factors that affect the quality of local government financial reports, such as HR competencies, SIPKD implementation, and the role of internal audit, with a sample of Brebes Regency BPKD employees. Data analysis involved validity, reliability, and classical assumption tests. The results show that the application of SIPKD and the role of internal audit have a positive and significant effect on the quality of government financial reports, while HR competencies have a negative but insignificant effect. Simultaneously, the three factors have a significant effect on the quality of local government financial reports.